Patient Satisfaction on the Assurance of Health Service Quality in the Independent Midwifery Practice During Covid-19 Pandemic - Menik Kustriyani; Heny Prasetyorini (Indonesian Journal of Global Health Research, 2021)
Healthcare providers must recognize the need to provide high-quality public health services. Customer service is critical since patients can choose services that meet their needs. In the midst of a pandemic, healthcare providers are becoming overburdened with cases of COVID 19. Health services must always protect both health personnel and patients. The purpose of this study was to determine patient satisfaction on the dimension of quality assurance. This study uses a descriptive analytic methodology with a cross-sectional approach. The participants in this study were obstetric patients, specifically family planning, prenatal, and intra-natal patients. There were 21 participants selected through consecutive sampling. This study has completed an ethical test at Universitas Widya Husada Semarang. This research is analyzed by descriptive method. The findings indicated that the population is between the ages of 26.61 – 32.72, regarded as early adulthood. The population's quality assurance dimension is between 55.94 – 59.59, which is deemed quite qualified. Based on the findings of the investigation, it was determined that the quality of service provided during the COVID-19 pandemic was adequate.